(untitled) (Advances in Applied Mathematics and Mechanics, 2019)
Considering primary and secondary regimes of creep, deformation of a rotating disc made of Al-SiC Functionally Graded Material (FGM) is investigated using Generalized Differential Quadrature Method (GDQ). Primary and secondary creep are described by Norton law in which creep parameters depended on volume fraction distribution of SiC reinforcement particles, temperature and particle size. All mechanical and thermal properties are functions of volume fraction percentage of SiC particles. Using equilibrium, constitutive and strain-displacement equations, displacement-based creep equation is obtained. This non-closed form equation is solved using GDQ method and a self-developed solution algorithm. Different graphs of creep strains and stresses are extracted using this presented method of creep analysis. Studies show that functionally distribution of particle content and prevailing temperature does not influence the stress fields considerably but obviously, the creep rates depend on temperature level and percentage of reinforcing particles.